Interplay of adipokines and myokines in cancer pathophysiology: Emerging therapeutic implications. - Dalamaga, Maria (World J Exp Med, 2013)
Excess body weight constitutes a worldwide health problem with epidemic proportions impacting on the risk and prognosis of several disease states including malignancies. It is believed that the metabolic changes associated with weight gain, particularly visceral obesity, and physical inactivity could lead to dysfunctional adipose and muscle tissues causing insulin resistance, low-grade chronic inflammation and abnormal secretion of adipokines and myokines. The complex paracrine and endocrine interconnection between adipokines and myokines reflects a yin-yang balance with important implications in processes such as lipolysis control, insulin sensitivity and prevention from obesity-driven chronic low-grade inflammation and cancer promotion through anti-inflammatory adipokines and myokines. Furthermore, the complex pathophysiology of cancer cachexia is based on the interplay between muscle and adipose tissue mediated by free fatty acids, various adipokines and myokines. The purpose of this editorial is to explore the role of the adipose and muscle tissue interplay in carcinogenesis, cancer progression and cachexia, and to examine the mechanisms underpinning their association with malignancy. Understanding of the mechanisms connecting the interplay of adipokines and myokines with cancer pathophysiology is expected to be of importance in the development of therapeutic strategies against cancer cachexia. Advances in the field of translational investigation may lead to tangible benefits to obese and inactive persons who are at increased risk of cancer as well as to cancer patients with cachexia.